2009
DOI: 10.1590/s1516-89132009000600015
|View full text |Cite
|
Sign up to set email alerts
|

Gills of juvenile fish piaractus mesopotamicus as histological biomarkers for experimental sub-lethal contamination with the Organophosphorus Azodrin®400

Abstract: Piaractus mesopotamicus is a freshwater native fish from rivers of the Paraná-Paraguay Basin and of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In Cirrhinus mrigala exposed to "Nuvan" at higher concentrations, appearance of aneurysm at an interval of 2 d and onward could cause the disruption/reduction in gaseous exchange capability and consequently weakening of the fishes. This corroborates with the views of Rudnicki et al (2009) [49] who reported aneurysm in secondary lamellae of the gills of Piaractus mesopotamicus exposed to Azodrin 400, an organophosphate. Machado and Fanta (2003) [37], in the gills of Metynnis roosevelti exposed to methyl parathion, an organophosphate, reported the collapse of the pillar cells followed by a loss of shape of the erythrocytes that can be considered to indicate osmotic and ionic alterations.…”
Section: Discussionsupporting
confidence: 92%
“…In Cirrhinus mrigala exposed to "Nuvan" at higher concentrations, appearance of aneurysm at an interval of 2 d and onward could cause the disruption/reduction in gaseous exchange capability and consequently weakening of the fishes. This corroborates with the views of Rudnicki et al (2009) [49] who reported aneurysm in secondary lamellae of the gills of Piaractus mesopotamicus exposed to Azodrin 400, an organophosphate. Machado and Fanta (2003) [37], in the gills of Metynnis roosevelti exposed to methyl parathion, an organophosphate, reported the collapse of the pillar cells followed by a loss of shape of the erythrocytes that can be considered to indicate osmotic and ionic alterations.…”
Section: Discussionsupporting
confidence: 92%
“…All the histological observations indicated that exposure to sublethal concentration of MCP caused degenerative effects such as dense fibrosis of gill filaments,[ 11 ] fusion and shortening of secondary lamellae,[ 31 32 ] fragmented columnar cells, and hypertrophy in mucous cells of foot tissue. These changes in normal tissue architecture lead to loss of normal physiological functions of animal.…”
Section: Discussionmentioning
confidence: 99%
“…The altered levels of antioxidant enzymes probably demonstrate a pollutant-induced toxic response in molluscs. [11] All the histological observations indicated that exposure to sublethal concentration of MCP caused degenerative effects such as dense fibrosis of gill filaments, [11] fusion and shortening of secondary lamellae, [31,32] fragmented columnar cells, and hypertrophy in mucous cells of foot tissue. These changes in normal tissue architecture lead to loss of normal physiological functions of animal.…”
Section: Mcp = Monocrotophos Lc = Lethal Concentrationmentioning
confidence: 99%